Differential Diagnosis and Treatment Rates Between Systolic and Diastolic Hypertension in Young Adults: A Multidisciplinary Observational Study. Issue 11 (13th June 2015) - Johnson, Heather M.; Bartels, Christie M.; Thorpe, Carolyn T.; Schumacher, Jessica R.; Pandhi, Nancy; Smith, Maureen A.
<x xml:space="preserve">Abstract</x> Differential rates of diagnosis and treatment by hypertension (HTN) type may contribute to poor HTN control in young adults. The objective of this study was to compare rates of receiving a hypertension diagnosis and antihypertensive agent among young adults with (1) isolated systolic, (2) isolated diastolic, and (3) combined systolic/diastolic HTN. A retrospective analysis was conducted in patients aged 18 to 39 years (n=3003) with incident HTN. Kaplan–Meier survival and Cox proportional hazards analyses were performed. Only 56% with isolated systolic HTN received a diagnosis compared with 63% (systolic/diastolic); 32% with isolated systolic HTN received an initial antihypertensive compared with 52% (systolic/diastolic). Compared with patients with systolic/diastolic HTN, those with isolated systolic HTN had a 50% slower diagnosis rate (hazard ratio [HR], 0.50; 95% confidence interval [CI], 0.41–0.60) and those with isolated diastolic HTN had a 26% slower rate (HR, 0.74; CI, 0.60–0.92). Patients with isolated systolic HTN had 58% slower medication initiation (HR, 0.42; CI, 0.34–0.51) and those with isolated diastolic HTN had 31% slower rates (HR, 0.69; CI, 0.55–0.86). Young adults with isolated systolic HTN have lower diagnosis and treatment rates.